Fitness test Polar vs Harvard test in evaluation of physical fitness for the selection of UPTC physical education program applicants (Impetus, 2021)
Objective: to compare the Harvard test against Fitness Polar test as a measure of cardiovascular capacity in the selection of applicants for the Physical Education program, Recreation and Sports of the Pedagogical University and Tecnológica de Colombia. Materials and methods: this inquiry It is quantitative, descriptive, without intervention, a non-probabilistic sample was made, consisting of by 38 physical education students, recreation and sports (32 men and 6 women), aged between 18 and 35 years. The tests were carried out in the same week and the data were processed in SPSS. Results: found in first instead, a Pearson correlation of 0.704 and significance at the 0.01 level (bilateral), between the Storer test and Fitness Polar test. Second, the 0.509 correlation between the Storer test and the Harvard test. This results Allow to conclude that the Polar Fitness test presents a greater correlation with VO2max, found by the test of Storer than the Harvard test. Conclusions: Fitness Polar test is more suitable and reliable to evaluate physical fitness and also offers a better and more detailed classification of applicants to the Physical Education Program, Recreation and Sports of the Pedagogical University and Tecnológica de Colombia.